2015
DOI: 10.1073/pnas.1510461112
|View full text |Cite|
|
Sign up to set email alerts
|

Evidence for extensive horizontal gene transfer from the draft genome of a tardigrade

Abstract: Horizontal gene transfer (HGT), or the transfer of genes between species, has been recognized recently as more pervasive than previously suspected. Here, we report evidence for an unprecedented degree of HGT into an animal genome, based on a draft genome of a tardigrade, Hypsibius dujardini. Tardigrades are microscopic eight-legged animals that are famous for their ability to survive extreme conditions. Genome sequencing, direct confirmation of physical linkage, and phylogenetic analysis revealed that a large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
198
3
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 169 publications
(207 citation statements)
references
References 55 publications
3
198
3
3
Order By: Relevance
“…The level of HGT that we infer remains higher than in most animals that have been tested (Fig. 1), although not as high a level as we had originally concluded (1).…”
contrasting
confidence: 40%
See 2 more Smart Citations
“…The level of HGT that we infer remains higher than in most animals that have been tested (Fig. 1), although not as high a level as we had originally concluded (1).…”
contrasting
confidence: 40%
“…This assembly was 252 Mb, larger than the 212.3-Mb assembly that we had used in our report (1), as pointed out correctly by others (5). The 212.3-Mb assembly used in our report is available at the link provided below.…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…Many species of Tardigrada can survive extreme conditions through cryptobiosis. In a recent paper [Boothby TC, et al (2015) Proc Natl Acad Sci USA 112(52):15976-15981], the authors concluded that the tardigrade Hypsibius dujardini had an unprecedented proportion (17%) of genes originating through functional horizontal gene transfer (fHGT) and speculated that fHGT was likely formative in the evolution of cryptobiosis. We independently sequenced the genome of H. dujardini.…”
mentioning
confidence: 99%
“…Hypsibius dujardini (Doyère, 1840) is a limnetic tardigrade that is an emerging model for evolutionary developmental biology (4,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). It is easily cultured in the laboratory, is largely see-through (aiding analyses of development and anatomy; SI Appendix, Fig.…”
mentioning
confidence: 99%